2020
DOI: 10.1155/2020/8838216
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Classification Method for Tunnel Lining Cracks Based on PFC-BP Neural Network

Abstract: Tunnel lining crack is the most common disease and also the manifestation of other diseases, which widely exists in plain concrete lining structure. Proper evaluation and classification of engineering conditions directly relate to operation safety. Particle flow code (PFC) calculation software is applied in this study, and the simulation reliability is verified by using the laboratory axial compression test and 1 : 10 model experiment to calibrate the calculation parameters. Parameter analysis is carried out f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…BP neural networks have powerful regression analysis capabilities and can predict quite accurate results after only a certain amount of data training [ 19 ].…”
Section: Machine Learning-based Approach To Teaching Physical Healthmentioning
confidence: 99%
“…BP neural networks have powerful regression analysis capabilities and can predict quite accurate results after only a certain amount of data training [ 19 ].…”
Section: Machine Learning-based Approach To Teaching Physical Healthmentioning
confidence: 99%
“…Various hyperparameters were used in the training process of the SRGAN and segmentation network because the SRGAN has a structure wherein the generator and discriminator compete with each other for learning. Two types of functions, namely the discriminator loss function (L D ) and generator loss function (L G ), were used for the loss function, with the discriminator loss function defned as in equation (3). Furthermore, the binary cross-entropy equation was used for L d,real and L d,fake .…”
Section: Methodsmentioning
confidence: 99%
“…Tunnel cracks may lead to future leakage and damage, signifcantly degrading the durability of the tunnel [1,2]. In addition, they can be considerably afected by environmental changes [3] and can even cause accidents. Terefore, cracks require regular and precise maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…In 1990, Picard et al 27 found that the division ratio of the training set, validation set, and training set, although not mandatory but has a certain impact on the evaluation performance, as can be seen from a large number of training studies on neural networks in recent years, most researchers have used a ratio of 80% for the training set and 20% for the rest. 30,31 For BP-ANN and its derivative models, this paper uses the ratio of the training set, validation set, and test set 8:1:1 to divide them, and for other neural network models, this paper uses the ratio of the training set to test set 8:2 to divide them.…”
Section: Description Of the Poa-bp Methodology And Comparison Of Trai...mentioning
confidence: 99%
“…From researchers’ studies, 30,31 it can be seen that the number of layers of the hidden layer structure of the neural network affects the prediction accuracy of the overall model as well as the computing time, especially for the prediction of the processing parameters of a very complex mechanical structure such as a pure electric vehicle power pack, it is more necessary to increase the number of layers of the structure of the neural network to improve the accuracy of the prediction, but too many layers will increase the difficulty of the calculation. This paper set up a single input layer with an output layer and increase the single hidden layer in order according to a sequence of equal differences with a tolerance of 1.…”
Section: Description Of the Poa-bp Methodology And Comparison Of Trai...mentioning
confidence: 99%